2017
DOI: 10.1016/j.repc.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Hypervolemia, hypoalbuminemia and mitral calcification as markers of cardiovascular risk in peritoneal dialysis patients

Abstract: Traditional CV risk factors appear to have little impact on CV complications in PD patients. Nevertheless, hypervolemia, hypoalbuminemia and mitral calcifications were independent predictors of CV events or mortality in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Hypoalbuminemia is also a risk factor for cardiovascular disease. 24,29 The present study demonstrated that serum albumin value in patients with IBIL ≥ 3.0 μmol/L was higher than that in patients with IBIL <3.0 μmol/L, which may have potentially increased the protective effect of IBIL which is albumin-bound. However, in multivariate Cox regression analysis, low IBIL was still an independent risk factor for cardiovascular events in MHD patients even after adjusting for serum albumin and other potential confounding factors.…”
Section: Discussionmentioning
confidence: 58%
“…Hypoalbuminemia is also a risk factor for cardiovascular disease. 24,29 The present study demonstrated that serum albumin value in patients with IBIL ≥ 3.0 μmol/L was higher than that in patients with IBIL <3.0 μmol/L, which may have potentially increased the protective effect of IBIL which is albumin-bound. However, in multivariate Cox regression analysis, low IBIL was still an independent risk factor for cardiovascular events in MHD patients even after adjusting for serum albumin and other potential confounding factors.…”
Section: Discussionmentioning
confidence: 58%
“…Although HVC is a risk factor for adverse CEs and cardiovascular mortality [3], different studies have different predictions. Some studies suggested that AVC and MVC are associated with adverse CEs, while some reported that both AVC and MVC are associated with higher rates of adverse CEs [6, 24, 25]. The cumulative incidence of CE-free survival in the HVC group was significantly lower than that in the non-HVC group.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that patients with a history of cardiovascular events had elevated markers of cardiovascular events and were more likely to have cardiovascular events than patients with cardiovascular disease [ 11 ]. Several studies have shown that hypoalbuminemia is a risk factor for cardiovascular events in peritoneal dialysis patients [ 8 , 17 ]. Hypoalbuminemia was shown to be related to malnutrition, protein loss, and inflammation that promotes atherosclerosis of blood vessels, leading to cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%